High-Fat Diet Induces Neuroinflammation and Mitochondrial Impairment in Mice Cerebral Cortex and Synaptic Fraction - Cavaliere, Gina; Trinchese, Giovanna; Penna, Eduardo; Cimmino, Fabiano; Pirozzi, Claudio; Lama, Adriano; Annunziata, Chiara; Catapano, Angela; Mattace Raso, Giuseppina; Meli, Rosaria; Monda, Marcellino; Messina, Giovanni; et al. (Frontiers in Cellular Neuroscience, 2019)
Brain mitochondrial dysfunction is involved in the development of neurological and neurodegenerative diseases. Mitochondria specifically located at synapses play a key role in providing energy to support synaptic functions and plasticity, thus their defects may lead to synaptic failure, which is a common hallmark of neurodegenerative diseases. High Fat Diet (HFD) consumption increases brain oxidative stress and impairs brain mitochondrial functions, although the underlying mechanisms are not completely understood. The aim of our study is to analyse neuroinflammation and mitochondrial dysfunctions in brain cortex and synaptosomal fraction isolated from a mouse model of diet induced obesity. Male C57Bl/6 mice were divided into two groups fed a standard diet or HFD for 18 weeks. At the end of the treatment, inflammation (detected by ELISA), antioxidant state (measured by enzymatic activity), mitochondrial functions and efficiency (detected by oxidative capacity and Seahorse analysis), and BDNF pathway (analyzed by western blot) were determined in brain cortex and synaptosomal fraction. HFD induces neuroinflammation and mitochondrial dysfunctions in brain cortex and synaptosomes. Indeed, in HFD animals we observed an increase in inflammatory parameters and oxidative stress and a decrease in mitochondrial oxidative capacity both in brain cortex and synaptosomal fraction. These alterations parallel with modulation of BDNF, a brain key signalling molecule that is linking synaptic plasticity and energy metabolism. Neuroinflammation HFD-dependent negatively affects BDNF pathway and mitochondrial activity in the brain cortex. The effect is even more pronounced in the synaptic region, where the impaired energy supply may have a negative impact on neuronal plasticity.